Lightweight block cipher algorithms: review paper - Salim, Sufyan; Taha Alshaikhli , Imad Fakhri; Sulaiman, Alyaa Ghanim (ER PUBLICATIONS, 2016)
Lightweight block cipher algorithms are very important for constraint environment. This paper analyses most of the known lightweight block cipher algorithms such as, HISEC, OLBCA, PRINCE, TWINE, KLEIN, LED, LBLOCK, PRINT, PRESENT through four factors (Algorithm specifications, S-boxes, Cost, Cryptanalysis). All the results have been presented.